Projekcije socialnodemografske, posestne in fizične preobrazbe naselja ob primeru Bevk - Gosar, Lojze (Geografski vestnik, 1983)
Population projections as a planner's tool are often questioned as to their reliability and usefulness. In our work on demographic projections we try to take into account the fact that demographic development is also spatially tied and directly affects settlement's physical and social make up. In this paper we are attempting to link demographic projections with the social, landownership and physical transformation of a small rural community (Bevke). This village is located in the immediate vicinity (14 km) of Ljubljana. The Bevke community has preserved its rural character in spite of the fact that the majority of its population is employed in nonagricultural sector. Because Ljubljana is so ealisy accessible, pressure for intensive residential growth in the next 20 years could be expected. If the development is not successfully planned, the community will loose its present qualities without acquiring new ones, and will become similar to many suburban places in this part of Slovenia. In our analysis the population capacity of suitable land surface for residential construction has served as the target number for the cohort survival population projection up to the year 2000. The main criteria for the delimitation of land use is the protection of agricultural land from the non-agricultural use, the avoidance of exaggerated and uncontrolled residential growth among others. One of the "target" population projection results is the needed annual number of immigrants. In the team work involving architects, geographers and ethnologist, two alternatives for future physical growth of the place were developed. Special interest was given to the dynamic planning approach according to which growth does not necessarily mean simply a loss of the present social, physical and other qualities of a place. Rather than preservationist's approach, which does not seem very effective, the social and physical fabric of the place should be enriched by new functions. Special attention was given to the possibility of the gradual formation of new farming units (lots) on the basis of land consolidation, considering as much as possible present land ownership, fragmentation and ecologic conditions.
Keywords: Bevke; demografija; poselitev; projekcija prebivalstva